#### Answer

$2\sqrt{3}$

#### Work Step by Step

$\sqrt{-2} \cdot \sqrt{-6} = \sqrt{(-2)(-6)} = \sqrt{12}=2\sqrt{3}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$2\sqrt{3}$

$\sqrt{-2} \cdot \sqrt{-6} = \sqrt{(-2)(-6)} = \sqrt{12}=2\sqrt{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.